Kritik Terhadap Narasi Gender Dalam Kitab Uqud Al-Lujain: Analisis Relevansi Hukum Keluarga Islam Kontemporer di Indonesia - Abdilla, Ahmad Farhan; Yusuf Baihaqi; Edi Susilo (Kartika: Jurnal Studi Keislaman, 2026)
This study is motivated by the issue concerning the relevance of gender narratives in the book Uqud al-Lujain by Shaykh Nawawi al-Bantani to the social developments of modern society. The book portrays husband–wife relations in a hierarchical manner and places women in a subordinate position, raising questions regarding its compatibility with the principles of equality in contemporary Islamic family law in Indonesia. This study aims to identify the forms of gender bias contained in the book and to analyze their compatibility with the Compilation of Islamic Law (Kompilasi Hukum Islam) and Law Number 1 of 1974 concerning Marriage.The research employs a qualitative method based on library research with a descriptive-analytical approach. The findings reveal three main forms of gender bias: restrictions on women’s freedom, the subordination of women within the household, and the legitimization of husbands’ disciplinary actions toward their wives. In the context of contemporary Islamic family law in Indonesia, these views are considered no longer fully relevant, as family relations have evolved toward more equal relationships characterized by mutual respect and the protection of individual rights. Therefore, a contextual reinterpretation of religious texts is necessary in order to create family relationships that are more just and balanced